Higher weight-adjusted waist index is associated with increased likelihood of kidney stones - Liu, Hangyu; Ma, Yang; Shi, Lungang (Frontiers in Endocrinology, 2023)
Abstract Objectives: The objective of this study was to evaluate the association between weight-adjusted waist index (WWI) and the prevalence of kidney stones among adults in the United States. Methods: The cross-sectional study utilized data from the National Health and Nutrition Examination Survey (NHANES) spanning the years 2007-2018. A total of 31,344 participants were categorized into two groups: those with kidney stones and those without. WWI was determined by dividing waist circumference (cm) by the square root of body weight (kg). To examine the relationship between kidney stones and WWI, multivariate logistic regression models, smoothed curve fitting, and weighted generalized additive model (GAM) regression were employed. Subgroup analysis and interaction tests were conducted to explore the stability of this association across different groups. Results: The final analysis comprised a total of 31,344 participants, including 2,928 individuals who had a history of kidney stones. In the fully adjusted model, an increase in WWI exhibited a positive correlation with the prevalence of kidney stones (OR=1.34, 95% CI: 1.18-1.51). When WWI was converted into quartiles (Q1-Q4), participants in the highest quartile (Q4) had a 69% greater risk of developing kidney stones compared to those in the lowest quartile (Q1) (OR=1.69, 95% CI: 1.28-2.25). This positive association was particularly notable among non-diabetic patients. Conclusions: Our study demonstrates a significant positive association between weight-adjusted waist index levels and an elevated prevalence of kidney stones among US adults. Furthermore, this research highlights the potential utility of weight-adjusted waist index in the prevention of kidney stones in the overall population. This relationship is limited and further research is needed to test this hypothesis.